2017
DOI: 10.1002/jnr.24184
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of neuroinflammation secondary to acute insults originated outside the brain

Abstract: The term "neuroinflammation" has been widely used to describe a series of acute or chronic conditions that cause inflammation in the central nervous system (CNS). Neurological damage can be a consequence of direct local injury or, secondary, of systemic or even distant inflammatory processes. In this respect, animal models have been developed to better understand the pathophysiology and, possibly, to evaluate more effective methods of treatment for these disorders. Animal models that promote alterations in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
0
8
0
1
Order By: Relevance
“…Emerging studies associate depression-like symptom with modulation of the immune system [ 20 ]. Indeed, recently, several models of systemic inflammation have been shown to cause astroglyosis, the increased proliferation of astrocytes (Reviewed in [ 21 ]). To determine whether the systemic inflammation and endothelial activation in tumor-bearing mice lead to astrocyte activation, we assessed levels of glial fibrillary acidic protein (GFAP), an intermediate filament protein used as astrocyte activation marker, in the whole cerebrum lysates from these mice.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging studies associate depression-like symptom with modulation of the immune system [ 20 ]. Indeed, recently, several models of systemic inflammation have been shown to cause astroglyosis, the increased proliferation of astrocytes (Reviewed in [ 21 ]). To determine whether the systemic inflammation and endothelial activation in tumor-bearing mice lead to astrocyte activation, we assessed levels of glial fibrillary acidic protein (GFAP), an intermediate filament protein used as astrocyte activation marker, in the whole cerebrum lysates from these mice.…”
Section: Resultsmentioning
confidence: 99%
“…TBI can cause emotional and cognitive impairment, epilepsy, loss of limb function, and memory impairment, which seriously affects the health of the brain. The development of brain injury after initial injury can significantly aggravate the deterioration and death rate of TBI patients, here called secondary brain injury (SBI) (Hamasaki et al, 2017 ). At present, little is known about the complex cellular response to the SBI and no effective treatment options are available, especially during its acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of several models for evaluating the therapeutic potential of molecules (73,74), the effects of sorafenib on neuroinflammation have rarely been studied in non-LPS models. To address this gap, we examined the effects of sorafenib on neuroinflammation in 5xFAD mice, a model of AD, which revealed that 3 consecutive days of treatments significantly reduced Ab-mediated astroglial activation but not microglial activation (Figure 8).…”
Section: Discussionmentioning
confidence: 99%